Corruption and growth: Exploring the investment channel - Mina Baliamoune-Lutz; Léonce Ndikumana (University of Massachusetts, Department of Economics, 2008)
This study investigates the impact of corruption on public and private investment in African countries as a way of exploring one channel through which corruption undermines growth. The empirical results indicate that corruption affects economic growth directly and through its impact on investment. We find that corruption has a negative and significant effect on domestic investment and that corruption affects public and private investment differently. The results indicate that corruption has a positive effect on public investment while it has a negative effect on private investment. The positive association between public investment and corruption supports the view that corrupt bureaucrats seek to increase capital expenditure (over maintenance expenditures) to maximize private gains (rent-seeking). In contrast, the results confirm that corruption discourages private investment, suggesting that corruption increases the costs of doing business while raising uncertainty over expected returns to capital. The results support the view that corruption hampers growth and call for institutional reforms to improve the quality of governance as a prerequisite for achieving investment-led growth.
Keywords: 330